2018
DOI: 10.1111/jar.12471
|View full text |Cite
|
Sign up to set email alerts
|

Parenting stress and depressive symptoms in Taiwanese mothers of young children with autism spectrum disorder: Association with children’s behavioural problems

Abstract: The findings indicated that one of the critical goals in early intervention for young children with ASD and their families is to reduce children's behavioural problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 51 publications
(82 reference statements)
0
22
0
3
Order By: Relevance
“…Our findings are consisted with those of previous studies demonstrating higher odds of emotional related symptoms in mothers of children with ASD when children had more behavioral problems. [26,43] Another finding of our study was that the social responsive problems of children were relevant to maternal anxiety symptoms. Begeer et al [44] found that high-stress levels lead to the development of depressive symptoms, but in their study, there were no associations between social responsive problems and maternal stress.…”
Section: Discussionmentioning
confidence: 68%
“…Our findings are consisted with those of previous studies demonstrating higher odds of emotional related symptoms in mothers of children with ASD when children had more behavioral problems. [26,43] Another finding of our study was that the social responsive problems of children were relevant to maternal anxiety symptoms. Begeer et al [44] found that high-stress levels lead to the development of depressive symptoms, but in their study, there were no associations between social responsive problems and maternal stress.…”
Section: Discussionmentioning
confidence: 68%
“…More specifically, parents of younger children with ASD experienced higher rates of depressive symptoms than parents of adolescents with ASD. Overall, due to heterogeneity of the instruments used to measure depressive symptoms, there is a wide variability in the rate of depressive symptoms . However, it has been well‐established that the caregivers of children with ASD tend to have a higher rate of depressive symptoms compared to normally developing children .…”
Section: Introductionmentioning
confidence: 99%
“…Overall, due to heterogeneity of the instruments used to measure depressive symptoms, there is a wide variability in the rate of depressive symptoms. [15][16][17] However, it has been well-established that the caregivers of children with ASD tend to have a higher rate of depressive symptoms compared to normally developing children. 18 Furthermore, the rate of depression among caregivers appears to outstrip the rate noted among the general population.…”
mentioning
confidence: 99%
“…The present study showed psychopathology in 80% mothers of ASD children. Data from ordinal regression model studies reported that higher anxiety and depression levels were found in mothers of children with severe ASD 5,17 . In the present study, even though depression was more in the mothers of children with severe ASD, results were not statistically significant.…”
Section: Discussionmentioning
confidence: 99%